Intelejensi Sosial Dalam Perspektif Quran - Nugroho, Taufik; Sarnoto, Ahmad Zain; Ulfa, Siti Maria (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2022)
This research is motivated by the phenomenon of the tendency of people who have experienced apathy, individualism, and have lost their social sensitivity. Society is trapped in an attitude of prioritizing personal desires and disregarding the interests of others so that contemporary problems are born in today's society. Every individual should not only be concerned with the benefit of himself, while he mentions the problems that exist in his environment. This study will examine the terms of the Qur'an which are related to social intelligence. In this research, we will present a random interpretation of several verses of the Qur'an that are relevant to the theme of the discussion. The method used in this research is literature study with a thematic interpretation approach. The results of this study will reveal verses in the al-Qur'an that are relevant and related to social intelligence.